Mesin Sterilisasi Masker Otomatis Berbahan Alkohol dan Ultraviolet Menggunakan Arduino dan LM35 - Ojak Abdul Rozak; Juhana Juhana; Heri Kusnadi; Bobik Setiawan (Jurnal Informatika Universitas Pamulang, 2023)
Sterilization is a process of eradicating microorganisms both viruses and bacteria. This Arduino-based mask sterilization machine aims to sterilize used masks so they can be reused, reduce the impact of used mask waste and save on the cost of buying new masks. This machine works in a way, used masks are put into the sterilizer, then the LM35 sensor will detect the temperature inside the tool and display it on the LCD. When the detected temperature is met, the injector pump assisted by a DC motor will spray the alcohol solution onto the surface of the mask, after which the timer will turn on and the mask will be irradiated by an ultraviolet lamp of 211320 lux for a duration of 15 minutes. The sterilization results had a presentation rate of killing bacteria of 75.92% and a percentage of killing yeast of 66.6%. after the irradiation process is complete it is indicated by a buzzer sound.